2004
DOI: 10.1007/s00213-003-1711-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fluoxetine on positive and negative affect in a clinic-based smoking cessation trial

Abstract: Rationale-Fluoxetine improves affect in clinical syndromes such as depression and premenstrual dysphoric disorder. Little is known about fluoxetine's influence on mood changes after quitting smoking, which often resemble sub-clinical depression.Objectives-The present study, a re-analysis of previously published data , examined fluoxetine's effect on changes in negative and positive affect following quitting smoking.Methods-Adult smokers (n=175) without clinically significant depression were randomized on a dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 38 publications
2
26
2
Order By: Relevance
“…There is as yet no evidence indicating that 5-HT neurotransmission is a critical neurological substrate for the process of smoking cessation per se or for a putative role in suppressing nicotine withdrawal in smokers administered NRT. Although our results do not support a moderating role of these specific serotonergic candidate gene variants on smoking cessation in treatment seeking smokers using NRT, it remains to be seen whether or not these genetic variants influence the efficacy of other agents such as SSRIs for smoking cessation, which have been associated with decreased craving and negative affect during quit attempts and may portend a modest benefit for smoking cessation (Cook et al, 2004;Killen et al, 2000;Niaura et al, 2002). Indeed, Killen et al (2000) demonstrated that paroxetine reduced tobacco craving, and Cook et al (2004) observed that fluoxetine was associated with lower negative and positive affect during periods of abstinence in smokers undergoing quit attempts.…”
Section: Discussioncontrasting
confidence: 80%
“…There is as yet no evidence indicating that 5-HT neurotransmission is a critical neurological substrate for the process of smoking cessation per se or for a putative role in suppressing nicotine withdrawal in smokers administered NRT. Although our results do not support a moderating role of these specific serotonergic candidate gene variants on smoking cessation in treatment seeking smokers using NRT, it remains to be seen whether or not these genetic variants influence the efficacy of other agents such as SSRIs for smoking cessation, which have been associated with decreased craving and negative affect during quit attempts and may portend a modest benefit for smoking cessation (Cook et al, 2004;Killen et al, 2000;Niaura et al, 2002). Indeed, Killen et al (2000) demonstrated that paroxetine reduced tobacco craving, and Cook et al (2004) observed that fluoxetine was associated with lower negative and positive affect during periods of abstinence in smokers undergoing quit attempts.…”
Section: Discussioncontrasting
confidence: 80%
“…Largely neglected has been the question of whether drug self-administration can help overcome pleasure deficits and instantiate positive emotions. In prior work (Werth Cook et al 2004b), we found that anhedonic smokers in early nicotine withdrawal were prone to cigarette cravings that were mediated by decreased positive mood, rather than by increased negative mood. Likewise, the current findings suggest that self-administering nicotine to enhance pleasure is at least as important an aspect of the depression-prone smoker's attachment to cigarettes as is the use of cigarettes to dispel negative mood.…”
Section: Discussionmentioning
confidence: 87%
“…Studies examining the effects of pharmacotherapies on affect have shown that fluoxetine (Cook, Spring, McChargue, Borrelli et al, 2004), bupropion (Shiffman et al, 2000), and transdermal nicotine (Strasser et al, 2005) elevate (or prevent reductions in) PA in the context of smoking cessation. Given the influence of low PA on outcome, these treatments may be especially useful for smokers with elevated anhedonic-depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%